The Effects of Glyphosate and Roundup® Herbicides on the Kidneys’ Cortex and the Medulla and on Renal Tubular Cells’ Mitochondrial Respiration and Oxidative Stress - Rayhana Rihani; Anne-Laure Charles; Walid Oulehri; Bernard Geny (Molecules)
Glyphosate (GP) and its derivatives are present in almost all environments and suspected to induce acute and chronic kidney injuries. This public health issue is relatively underexplored. We therefore conducted an investigation on rats and tubular HK2 cells cultured for 24 h to determine whether GP’s and Roundup’s® (RU) potential renal toxicity might be related to mitochondrial respiration impairment and the increased production of hydrogen peroxide (H2O2) in both the renal cortex and medulla (involved in filtration and reabsorption, respectively) using a high-resolution oxygraph (Oxygraph-2K, Oroboros instruments). GP alone decreased maximal uncoupled mitochondrial respiration in the medulla (−14.2%, p = 0.02). RU decreased mitochondrial respiratory chain complexes I and I + II and the maximal respiratory capacity both in the renal cortex (−13.5%, p = 0.04; −20.1%, p = 0.009; and −14.7%, p = 0.08, respectively) and in the medulla for OXPHOS I + II (80.82 ± 7.88 vs. 61.03 ± 7.67 pmol/(s·mL), −24.5%, p = 0.003). Similarly, in HK2 cells, the decrease in OXPHOS CI + II was greater after RU (65.87 ± 1.30 vs. 51.82 ± 3.50 pmol/(s·mL), −21.3%, p = 0.04) compared to GP. Increased H2O2 production was mainly observed after RU in the medulla (+14.3% in OXPHOS CI + II, p = 0.04) and in HK2 cells (+19% in OXPHOS CI + II, p = 0.02). In conclusion, although the medulla might be more prone to GP-related mitochondrial damage, RU toxicity was greater in both the renal cortex and medulla and in cultured tubular HK2 cells. Enhancing mitochondrial respiration and reducing oxidative stress might favor the prevention of or reduction in such worldwide-used herbicides’ deleterious effects on the kidneys.